A Necessity for Sex Difference Researchers: A Review of David C. Geary, Male, Female: The Evolution of Human Differences (2nd ed.). American Psychological Association: Washington, D.C., 2009, ISBN 9781433806827 - LI, Norman P. (Institutional Knowledge at Singapore Management University, 2010)
Male, Female: The Evolution of Human Differences (2nd ed.), written by University of Missouri Curators' Professor and Thomas Jefferson Professor David C. Geary, is the long-awaited update to a classic treatise on sex differences originally published in 1998. The new edition has been largely expanded (by 171 pages) and summarizes much of the research relating to sex differences that has surfaced in the last 12 years. The book begins with a review of the broad processes of natural and sexual selection (Chapters 1–4) and then covers sexual selection in primates before moving on to humans (Chapter 5). The book then reviews work on fatherhood (Chapter 6), mate choice and mate competition (Chapters 7 and 8), cognition (Chapter 9, 12, 13), and child development (Chapters 10 and 11). In chapters 10 to 13, the theoretical groundwork laid in the first half of the book comes together with sex difference research in behavior, brain development, and hormones.